Home as a place for giving birth—A circumpolar study of the experiences of mothers and midwifes. Issue 2 (1st February 2019) - Clancy, Anne; Gürgens Gjaerum, Rikke
Abstract: This article explores what home birth mothers and midwives say about the birth experience and the interaction between mother, partner and midwife. It is based on an explorative empirical study of the narratives of seven home birth mothers and the experiences of five midwives. The authors examine how these subjective experiences can help us to understand the phenomenon of home birth. The article is grounded in a philosophy of place and feminist theory, understood within a health promotion framework. Home birth manifests itself as a place-based esthetic experience characterized by gender, body, nature and culture. The participants spoke of the significance of giving birth at home. The authors discover that giving birth at home involves celebration, togetherness and ontological security. It also encompasses a broad understanding of risk, power structures, responsibility and co-determination. Openness about the challenges of home births can boost the position of home birth among both clinicians and the general public.